Not obvious manifestation of extragenital lichen sclerosus in a child: a case report and literature review - Woźna, Julia; Łabędź, Nina; Bowszyc-Dmochowska, Monika; Dańczak-Pazdrowska, Aleksandra; Polańska, Adriana (Dermatology Review/Przegląd Dermatologiczny, 2025)
Lichen sclerosus is a chronic inflammatory skin disorder that primarily affects the anogenital region, but can also present in extragenital areas. In children, lichen sclerosus most commonly involves the vulvar and perianal regions, while extragenital manifestations are rare and often underrecognized. Lichen sclerosus may coexist or even overlap with other autoimmune skin disorders such as vitiligo or morphea. In cases where clinical differentiation is challenging, a skin biopsy is recommended to establish a definitive diagnosis. This report describes a rare case of an 11-year-old girl presenting with both vulvar and acral extragenital lichen sclerosus, accompanied by vitiligo patches on the eyelids. Although histopathological findings were inconclusive, clinical correlation supported the diagnosis of coexisting lichen sclerosus and vitiligo. This case highlights the importance of recognizing atypical presentations of lichen sclerosus in pediatric patients and underscores the need for comprehensive evaluation when multiple autoimmune skin disorders coexist.